Pengaruh Self Esteem dan Trust Terhadap Self Disclosure Pada Pengguna Aplikasi Kencan Online - Andriani, Iin (MOTIVASI, 2020)
This study aims to measure the effect of self esteem and trust on self disclosure of online dating application users. The sample of this research is 325 respondents. This sampling technique uses quota sampling technique. Research data were collected using three types of questionnaires that measure self disclosure, self esteem and trust. Data analysis techniques using the Spearman correlation with the help of the statistical program SPSS 23 for Windows. The results showed that there was a significant correlation between self esteem and self disclosure with a rho value of 0.394. And there is a significant correlation between trust and self disclosure with a rho value of 0.475. With a significant level of 0,000 (p <0.01). In this case self-esteem affects self-disclosure by 15.5%, while trust affects self-disclosure by 22.5%.